2014
DOI: 10.1371/journal.pone.0097646
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome, Alcohol Consumption and Genetic Factors Are Associated with Serum Uric Acid Concentration

Abstract: ObjectiveUric acid is the end product of purine metabolism in humans, and increased serum uric acid concentrations lead to gout. The objective of the current study was to identify factors that are independently associated with serum uric acid concentrations in a cohort of Czech control individuals.MethodsThe cohort consisted of 589 healthy subjects aged 18–65 years. We studied the associations between the serum uric acid concentration and the following: (i) demographic, anthropometric and other variables previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 50 publications
(64 reference statements)
6
29
0
1
Order By: Relevance
“…Our data is consistent with previously published experimental evidence supporting a causal role of ATP or uric acid signaling in liver inflammation caused by acetaminophen or by ischemia-reperfusion injury [8, 24, 25], and are further supported by evidence showing correlation between hyperuricemia and metabolic syndrome or long-term consumption of ethanol [26, 27]. Importantly, our data is consistent with a report by Shulga et al [28] demonstrating that activation of murine Kupffer cells by ethanol requires NLRP3, a ligand-sensing component of inflammasomes that detects ATP and uric acid [5].…”
Section: Discussionsupporting
confidence: 93%
“…Our data is consistent with previously published experimental evidence supporting a causal role of ATP or uric acid signaling in liver inflammation caused by acetaminophen or by ischemia-reperfusion injury [8, 24, 25], and are further supported by evidence showing correlation between hyperuricemia and metabolic syndrome or long-term consumption of ethanol [26, 27]. Importantly, our data is consistent with a report by Shulga et al [28] demonstrating that activation of murine Kupffer cells by ethanol requires NLRP3, a ligand-sensing component of inflammasomes that detects ATP and uric acid [5].…”
Section: Discussionsupporting
confidence: 93%
“…Previous genetic studies have demonstrated the associations between alcohol use and UA in humans . To the best of our knowledge, our study is the first to perform a Mendelian randomization analysis showing a potential causal association of increased alcohol use and higher UA.…”
Section: Discussionmentioning
confidence: 67%
“…This may have influenced the overall difference in parameters relevant to CADs. Second, we could not completely rule out all possible factors that may influence s-UA levels, including chronic kidney disorders, genetic disorders of purine metabolism, cardiovascular diseases, food intake, metabolic syndrome, and alcohol consumption 27,36,37. However, even after adjusting for possible and major confounding factors (age, gender, BMI, and smoking index), logistic regression analysis showed that s-UA levels continued to be an independent predictor of AL risk.…”
Section: Discussionmentioning
confidence: 99%